Molecular epidemiological investigation of G6PD deficiency in Yangjiang region, western Guangdong province - Liang, Hong-Feng; Cao, Yan-Bin; Lin, Fen; Yang, Yi-Kang; Liao, Yu-Wei; Ou, Wei-Hao; Chen, Jin-Ling; Zeng, Yan-Qing; Huang, Yu-Chan; Zeng, Guang-Kuan; Chen, Zhi-Xiao; Situ, Jing-Wei; et al. (Frontiers in Genetics, 2024)
Objectives: The prevalence of G6PD deficiency has not been reported in Yangjiang, a western city in Guangdong province. This study aims to investigate the molecular characteristics of G6PD deficiency in this region.Methods: Blood samples were collected from adults at a local hospital to screen for G6PD deficiency. The deficient samples were subjected to further analysis using PCR and reverse dot blot to determine the specific G6PD variants.Results: Among the 3314 male subjects, 250 cases of G6PD deficiency were found using the G6PD enzyme quantitative assay, resulting in a prevalence of 7.54% (250/3314) in the Yangjiang region. The prevalence of G6PD deficiency in females was 3.42% (176/5145). Out of the 268 cases of G6PD deficiency tested for G6PD mutations, reverse dot blot identified 20 different G6PD variants. The most common G6PD variant was c.1388G＞A (81/268), followed by c.1376G＞T (48/268), c.95A＞ G (32/268), c.1024C＞T (9/268), c.392G＞T (7/268), and c.871G＞A/c.1311C＞T (6/268). It was observed that c.871G＞A was always linked to the polymorphism of c.1311C＞T in this population.Conclusion: This investigation into G6PD deficiency in this area is expected to significantly improve our understanding of the prevalence and molecular characterization of this condition.